2015
DOI: 10.1039/c5ta04573h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic H2evolution over noble-metal-free NiS cocatalyst modified CdS nanorods/g-C3N4heterojunctions

Abstract: In this report, the CdS nanorods/g-C 3 N 4 heterojunctions loaded by noble-metal-free NiS cocatalyst were firstly fabricated by in situ hydrothermal method. The as-synthesized heterostructured photocatalysts were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), high-resolution 10 transmission electron microscopy, UV-visible spectroscopy, nitrogen absorption, photoluminescence (PL) spectra, transient photocurrent responses and electrochemical impedance spectroscopy (EIS) measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(160 citation statements)
references
References 77 publications
(204 reference statements)
7
151
0
Order By: Relevance
“…Note that this value can compare with the 1.0 wt% Pt loaded g-C 3 N 4 for H 2 generation (8.2 mol h -1 ) under otherwise same conditions [57]. In addition, nickel and cobalt compounds, such as cobaloxime [109], NiS [110,111] and NiS 2 [112] have also been demonstrated as co-catalysts to improve the H 2 evolution of g-C 3 N 4 under visible light irradiation. These works show the great potential of utilizing low cost transitional metal compounds as co-catalyst to substitute the noble metals in boosting the photocatalytic H 2 production of g-C 3 N 4 .…”
Section: Page 26 Of 46mentioning
confidence: 70%
“…Note that this value can compare with the 1.0 wt% Pt loaded g-C 3 N 4 for H 2 generation (8.2 mol h -1 ) under otherwise same conditions [57]. In addition, nickel and cobalt compounds, such as cobaloxime [109], NiS [110,111] and NiS 2 [112] have also been demonstrated as co-catalysts to improve the H 2 evolution of g-C 3 N 4 under visible light irradiation. These works show the great potential of utilizing low cost transitional metal compounds as co-catalyst to substitute the noble metals in boosting the photocatalytic H 2 production of g-C 3 N 4 .…”
Section: Page 26 Of 46mentioning
confidence: 70%
“…The enhanced current signals show that the catalysts have higher electron‐transfer efficiencies. In addition, electrochemical impedance spectroscopy showed that RCNO has the lowest resistance (see the Supporting Information, Figure S8), which further confirmed the enhanced charge transfer rate.…”
Section: Resultsmentioning
confidence: 99%
“…Bimetallic cocatalysts such as PtCo, [205] PdAu, [239] PtOAu [240] have exhibited higher H 2 photocatalytic activity than single noble metals. So far, numerous nonnoble metal cocatalysts have proven efficient in enhancing the photo catalytic H 2 generation activity of gC 3 N 4 , including FeO x , [228] MoS 2 , [229,[241][242][243][244] WS 2 , [245] NiS, [246][247][248] Ni 12 P 5 , [249] carbon nanotube (CNT), [232] carbon black, [233] carbon nanofiber, [222] Co(OH) 2 , [250] Ni(OH) 2 , [251,252] Cu(OH) 2 , [253] Ni(dmgH) 2, [254] and Ni [208,255,256] (Table 3). So far, numerous nonnoble metal cocatalysts have proven efficient in enhancing the photo catalytic H 2 generation activity of gC 3 N 4 , including FeO x , [228] MoS 2 , [229,[241][242][243][244] WS 2 , [245] NiS, [246][247][248] Ni 12 P 5 , [249] carbon nanotube (CNT), [232] carbon black, [233] carbon nanofiber, [222] Co(OH) 2 , [250] Ni(OH) 2 , [251,…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%